Miscibility in cyclic poly(butylene terephthalate) and styrene maleimide blends prepared by solid-dispersion and in situ polymerization of cyclic butylene terephthalate oligomers within styrene maleimide - Samsudin, Sani Amril (Wiley Periodicals, 2012)
Blends of cyclic butylene terephthalate oligomers (CBT) and styrene maleimide (SMI) were prepared by a solid dispersion technique in various compositions ranging from 90 to 10 wt % of CBT. In situ polymerization of the oligomers in the blend at 190 degrees C produced a blend of cyclic poly(butylene terephthalate) (c-PBT) and SMI. The blends were characterized by a variety of techniques including differential scanning calorimetry (DSC) and scanning electron microscopy (SEM). It was found that the presence of 30 wt % and above of SMI impeded the crystallization of c-PBT to such an extent that crystallization could not be detected under the conditions of the DSC experiment. The blend system exhibited a single composition-dependent glass transition temperature (Tg), which indicated the presence of miscibility.